AN OUTLOOK ON THE MECHANISMS OF DRUG INTERACTIONS WITH OTHER DRUGS, FRUITS, HERBS AND THEIR PREVENTIVE MEASURES - Rajan, ASHA K; K, Kousalya; Nathan B, Senthil; P, Valentina (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Drugs taken by a person are affected by a number of ways. A number of interactions are known to affect the drugs, change its efficacy or result in toxicity. Habits of a common person could also cause such interactions. Most of the people have habits of smoking, consumption of alcohol and taking dietary supplements without the advice of their physicians. Some drug interactions such as those between drug-herbs and drug-citrus fruit would bring us shock; even small fruit could sometimes bring adverse drug reactions to occur in our body. Due to drug interactions, there would sometimes be an increase or decrease in the efficacy of a drug. Being a pharmacist, it would be their ultimate role to check at a person’s hygienic record, looking and gathering information of the past recorded drugs, dietary supplements, hereditary diseases, etc. They would have to gather information about the recently releasing drugs and know complete information on the reactions which occur on their administration. Knowledge to people about herbal and food-drug interactions is very less. They take them to be natural and do not care about its consequences. However, this interaction depends on the amount and the potency of pharmacologically active ingredient present in the compounds. These herbal drugs are known to contain a varying number of phytochemicals which may cause a change to the transporters, enzymatic systems, causing failure of the therapeutic effect of the drug interactions. The elimination of some particular drugs is also affected due to these interactions. As a result of this interaction, a number of drugs which had taken birth had quickly been removed from the US markets. Thus, the ways for a person to avoid these interactions can only be the above mentioned advices given by the health practitioners, not to administer drugs by self-medication methods, taking a note of all the additional supplements taken by a patient to his physician, so that there is a clear picture about the interactions at their initial stage. (1) There are various drug interactions with a number of factors. (2) Unless there is clear knowledge about the pathway of drug elimination, drug interaction stands to be very difficult to be avoided. Keywords: Drug-food interactions, Pharmacokinetic, Pharmacodynamic, Drug-drug interactions. Â